Heavy Metal Contamination of Green Leafy Vegetables Cultivated in Residential Gardens in Enugu Urban, South East Nigeria - Joshua I. Ume; Chigozie B. Ichu; Nnenna S. John (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
The accumulation of some essential (Cu, Mn and Zn) and toxic metals (Cd and Pb) in cultivated vegetablesTelfairia occidental is (fluted pumpkin), Talinum triangulare (water leaf), Amaranthus viridis (green vegetable), and Vernonia amygdalina (bitter leaf) was investigated. The vegetables were cultivated in residential gardens in Enugu metropolis, the capital of Enugu State, South-East, Nigeria. Samples of these vegetables were randomly collected from three residential areas, dried, digested and analyzed for heavy metals using Buck 210VGP atomic absorption spectrophotometer. The relative abundance of the metals in the vegetables followed the sequence: Zn (2.28 mg/kg) > Mn (0.91 mg/kg) > Cu (0.45 mg/kg) > Pb (0.3 mg/kg) > Cd (0.05 mg/kg). The concentration levels of all the metals examined were within the FAO/WHO, Indian and the European Union (EU) recommended limits for metals in vegetables obtained from all the residential gardens. This implies that long term consumption of these vegetables does not pose any health risk to the inhabitants of Enugu urban. However, the presence of the metals indicates the gradual accumulation of heavy metals in leafy vegetables. Residential gardens should therefore not be sited close to main roads to avoid metal pollution from traffic emissions. Environmental authorities should prohibit the indiscriminate location of automobile repair shops contiguous to residential areas not only in Enugu Urban, but elsewhere across the country. The results showed that these vegetables are the good sources of essential trace metals.